A comparison of crude oil hydrocarbon mobilization by vaporization gas drive into methane, ethane, and carbon dioxide at 15.6 MPa and 42 °C. (1st August 2019) - Hawthorne, Steven B.; Miller, David J.
Abstract: An innovative sampling method was developed that allowed crude oil hydrocarbons dissolved in the upper gas-rich phase to be collected and quantitatively measured while maintaining constant reservoir conditions of 15.6 MPa and 42 °C. Crude oil was allowed to come to equilibrium with the injected gas phase (ca. 1/1 vol ratio) prior to collecting the dissolved hydrocarbons via a heated flow restrictor and analyzing them using high-resolution gas chromatography. As solvents, the three fluids' efficacy parallel their minimum miscibility pressures (MMPs) for the test crude oil. Methane (MMP = 28.1 MPa) was a very poor hydrocarbon solvent, and was only able to dissolve ca. 18 mg oil/g methane. In contrast, CO2 (MMP = 9.68 MPa) dissolved up to 133 mg oil/g CO2 and ethane (MMP = 5.27 MPa) dissolved 722 mg oil/g ethane. Sequential collections of the dissolved oil hydrocarbons in the gas-dominated phase showed progressively lower concentrations for ethane and CO2, which demonstrated that liquid/liquid partitioning (and not saturation solubility) between the gas-dominated and oil-dominated phases controls the amounts of dissolved hydrocarbons. Thus, the lower the ratio of injected ethane or CO2 to the bulk crude oil, the higher the dissolved hydrocarbon concentrations. Both methane and CO2 showed a bias against dissolving heavier hydrocarbons. Methane was only capable of dissolving the lightest hydrocarbons (up to about C12), while CO2 preferentially dissolved light and middle hydrocarbons (up to about C16), leaving a residual oil rich in higher molecular weight hydrocarbons with significantly higher viscosity and density (lower API gravity) than the original unexposed crude oil. In contrast, ethane was capable of efficiently dissolving the entire range of hydrocarbons, with only a small bias against the heavier hydrocarbons. These lab studies show that, at the constant reservoir pressure and temperature used, ethane is a far superior hydrocarbon solvent for crude oil hydrocarbons than CO2, while CO2 is far superior to methane. Thus, ethane may ultimately yield higher oil recovery efficiencies (used either instead of CO2 or after a CO2 flood), while reducing the deposition of paraffinic and other higher molecular weight hydrocarbons in the reservoir.